Reliability Analysis of Communication Network Service Quality For Internet of Vehicles (IoV) - Nizirwan Anwar; Dewanto Rosian Adhy; Budi Tjahjono; Rudi Hermawan; Nur Widiyasono; Muhammad Abdullah Hadi (Publisher Cv. Inara, 2021)
The development of the Internet of Vehicle (IoV) is overgrowing toward driving comfort, safety, and efficiency. Autopilot or a car without a driver is one implementation of IoT. To run the full function of IoV, a reliable communication network is needed because the risk will be substantial due to the low quality of network infrastructure services. In this research, we will analyze the quality of network infrastructure services. The analysis can be done through two approaches: direct measurement in the field using a GPS Tracker-based system and modeling using the mathematical function of transmit power of mobile communication transmitting devices. The test is carried out in a specific area with a sample of high traffic and low-density areas. This method was chosen to find the right pattern in measuring the quality of communication network services. The tests carried out produce dynamic data on service quality in certain areas. For areas of low density, the service quality tends to be below as well, and many areas without signal are found, while for areas with high density, the quality of service is found to be good, but network overload conditions often occur.